2020
DOI: 10.3390/en13246596
|View full text |Cite
|
Sign up to set email alerts
|

Anode Modification as an Alternative Approach to Improve Electricity Generation in Microbial Fuel Cells

Abstract: Sustainable production of electricity from renewable sources by microorganisms is considered an attractive alternative to energy production from fossil fuels. In recent years, research on microbial fuel cells (MFCs) technology for electricity production has increased. However, there are problems with up-scaling MFCs due to the fairly low power output and high operational costs. One of the approaches to improving energy generation in MFCs is by modifying the existing anode materials to provide more electrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 154 publications
0
20
0
Order By: Relevance
“…While the majority of previous research focused on the use of carbon-based materials and metal/metal oxides. 68,[76][77][78] Over years, these conventional materials were phased out in favor of more advanced materials that showed efficient MFC performance. The conventional carbonbased materials, shown in Fig.…”
Section: The Inuence Of Mfc Conguration On Biolm Formationmentioning
confidence: 99%
“…While the majority of previous research focused on the use of carbon-based materials and metal/metal oxides. 68,[76][77][78] Over years, these conventional materials were phased out in favor of more advanced materials that showed efficient MFC performance. The conventional carbonbased materials, shown in Fig.…”
Section: The Inuence Of Mfc Conguration On Biolm Formationmentioning
confidence: 99%
“…However, carbon electro corrosion becomes one of the performance reductions issues. In this regard, numerous studies have demonstrated that carbon‐based especially graphene can reduce corrosion issues, especially on metallic bipolar plates in fuel cell application 150,151 . This is related to graphene which has a very stable factor of outstanding physical and chemical properties, such as its high specific surface area (2630 m 2 g −1 ) outstanding electrical conductivity, and extraordinary biocompatibility on graphene all this can be used to solve corrosion issues with a simple solution.…”
Section: Current Problems and Future Developmentmentioning
confidence: 99%
“…2010; Nosek et al . 2020). Recent studies were focused on use of carbon nanotube and graphene as carbon material in electrode to enhance the surface area leading to good biofilm formation with efficient exoelectron transfer (Fan et al .…”
Section: Introductionmentioning
confidence: 99%